The Relationship between Marketing Blackmail and Sudanese Consumer Purchasing Intention - Mufadil, Babiker Alissa (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aimed to identify the relationship between marketing blackmail and Sudanese consumer purchasing Intention. The random sample of the study consists of 100 customers who purchase tea and coffee from coffee shops owned by women in Sudan. 67 of the questionnaire were returned and valid for analysis. A statistical test such as correlation analysis was applied and hypothesis was tested by using SPSS program. The study came out with some results; it found a weak relationship between marketing blackmail by women who sell tea and customer intention to re- Purchase. The study has reached a set of recommendations that include the customer consciousness less of marketing blackmailing methods by women sellers, and other emotional blackmail because of psychological, social and economic effects for customer as well as negative impact on the community.